Sistem Monitoring Intensitas Cahaya dan Suhu Air Aquascape Menggunakan Internet of Things - Pramudya Aziz Wisnuadi Wisnuadi; Rudi Susanto; Pramono (G-Tech: Jurnal Teknologi Terapan, 2024)
Maintaining water quality and light intensity in aquascape is often a challenge due to changing environmental conditions. The main problem in this research is how to monitor and regulate light intensity and water temperature automatically to support the survival of biota in aquascape. This research develops an Internet of Things (IoT) based monitoring system that uses DS18B20 sensor to monitor water temperature and GY-302 BH1750 sensor to monitor light intensity. Data from the sensors is sent to the ESP32 microcontroller which processes the data and controls the output in the form of LED lights, DC fans, and heaters. This tool is also equipped with notifications through the Blynk application on smartphones, so that users can monitor aquascape conditions in real-time. Prototype development method is used in this research with data collected through observation and literature study. The results show that this tool is able to monitor water quality and aquascape environment accurately and provide automatic notifications, so as to maintain optimal conditions for the biota in it.